Transfer of genes into hematopoietic cells using recombinant DNA viruses. - Karlsson, S (1985)
The ability of recombinant DNA viruses to transfer genes into hematopoietic cells has been explored. A recombinant simian virus 40 (SV40) in which the early region had been replaced with the chloramphenicol acetyltransferase (CAT) gene driven by the promoter from Rous sarcoma virus (RSV), was constructed. This virus transferred the CAT gene more efficiently into mouse and human bone marrow cells and into the K562, MEL, and WEHI hematopoietic tissue culture cell lines, than the classical calcium phosphate DNA transfer procedure, as shown by assay for CAT activity 48 hr after infection. Recombinant SV40 virions were also shown to be capable of stably transforming Chinese hamster ovary cells by use of an early region recombinant containing the methotrexate-resistant dihydrofolate reductase (DHFR) gene driven by the RSV promoter. The entire DHFR transcriptional unit could be detected in the genome of transformed cells that were also shown to be resistant to methotrexate. A recombinant adenovirus stock containing the neomycin-resistance gene driven by the SV40 early promoter was used to infect the K562 and MEL hematopoietic cell lines to resistance to the antibiotic G418. Transformation frequency was 10- to 100-fold higher than that obtained with calcium phosphate-precipitated DNA. Most or all of the recombinant adenovirus genome was integrated as 1-3 copies in the transformed cells. These studies show the feasibility of using DNA viruses for introduction of new genetic material into hematopoietic cells.